If I'm reading this correctly, it is 2*3*n*n = 6n^2
6n^2 = 54 Divide by 6
n^2 = 54/6
n^2 = 9 Take the square root of both sides.
sqrt(n^2) = sqrt(9)
n = +/- 3
n = + 3 or n = -3. Both will solve the equation above.
Edit
2 * 3 * n * n
Let n = 3
2 * 3 * 3 * 3 = 6 * 9 = 54
The other value is n = - 2
2 * 3 * n * n
2 * 3 * (-3) * (-3) A minus times a minus is a plus.
2 * 3 * 9 = 6 * 9 = 54
both + 3 and - 3 for n will give 54.
Answer:
3x^2-x+5.2f\left(-3\right)-f\left(4\right) =
3x^2-x-19.6f
Step-by-step explanation:
3x^2-x+5.2f\left(-3\right)-f\left(4\right)
=3x^2-x-5.2f\cdot \:3-f\cdot \:4
=3x^2-x-15.6f-4f
=3x^2-x-19.6f
Answer:
X is just the variable or missing edge, side, angle .etc that you are looking for
Step-by-step explanation:
Answer:
7x
Step-by-step explanation:
It equals 28 just like the problem with parentheses, 7x .
Answer:
Top Left
I sincerely hope this is right and that you get g really good mark ;)